NILAI-NILAI EDUKASI DALAM KERAJINAN LONTAR DI DESA SURADADI KECAMATAN TERARA LOMBOK TIMUR - Baiq Saipinatun Naja; Habibuddin; Muchammad Tryianto; Husnul Mukti (STKIP Subang, 2024)
Palmyra crafts in Suradadi Village, Terara District, East Lombok, are not widely known as a source of educational value. This study aims to reveal educational values and their implementation in palmyra crafts in the village. The approach used is qualitative narrative with observation, interview, and documentation methods. The subjects of the study included village officials, craftsmen, and the surrounding community. Data validity tests were carried out through the degree of trust, transferability, dependency, and certainty. Data were analyzed using the Miles & Huberman interactive model, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) The forms of palmyra crafts in Suradadi Village, which began to develop since the 1950s, include tebolaq, sopaq, bale bottles, pencil cases, wall toys, bags, and hats, each with its own uniqueness nd characteristics; (2) Palmyra crafts act as a side job, increase creativity, and fill the free time of housewives, and function in preserving culture, daily use, and adding aesthetic value; (3) Educational values in palm leaf crafts include moral, social, aesthetic, economic, creativity, cultural preservation, cooperation, perseverance, and precision, which influence the character of the community, especially in changing traditional views on the role of women. The implementation of these values is seen in the daily interactions of the craftsmen, strengthening togetherness and creativity.